A Supplement to the Aquatic and Swampy Vegetation of Gorakhpur - Sahai, R.; Sinha, A. B. (Indian Forester, 1968)
The present paper is a supplement to the "Ecological studies on Aquatic and Swampy Vegetation of Gorakhpur-a Survey" (Sen, 1959). The authors have collected and identified additional forty-eight species of plants from the various lakes, ponds, swamps and low lying areas existing in their vicinity in the District. Out of the 48 species enumerated in the present paper, 2 belong to Pteridophytes, 20 to Monocotyledons and the remaining 26 to Dicotyledons.